Analysis of the influence of aerodynamic qualities of the components of mixtures on separation in power-saving vortex vehicles - Knaub, Ludmila (Technology audit and production reserves, 2020)
The object of research is gas-dynamic vortex processes in heterogeneous polydisperse flows. One of the most problematic issues is the determination of the aerodynamic characteristics of the components of a heterogeneous polydisperse medium, which are necessary to create a mathematical model of the separation process. The study used methods of mathematical modeling based on the theory of similarity. A technique has been developed for assessing the aerodynamic parameters of mixture components, on the basis of which a number of aerodynamic similarities have been compiled. The coefficients of lift, aerodynamic drag, lateral force, longitudinal, transverse and rotational moments of the components of the grain mixture are obtained. This is necessary for theoretical studies of gas-dynamic processes in vortex separators in unsteady three-dimensional flow with variable flow density, concentration and flow rate of the separated mixture components and the carried fractions. The Reynolds vibration criterion is obtained, based on which the trajectories and energy of the vortex motion of individual components and the separation degree of heterogeneous mixtures are determined. This allows to improve the mathematical model of the distribution process of heterogeneous polydisperse mixtures in the proposed energy-saving vortex separators. The obtained results provide the basis for improving the general theory of heterogeneous vortex flows by introducing an external disturbance criterion that takes into account the drag of the vortex force field and the amplitude-frequency energy level. Thanks to this, it is possible to evaluate the influence of any argument in the desired function. The research results make it possible to automate the analysis of process characteristics and compare them by parameters with experimental data. And also to evaluate the correspondence of dynamic, kinematic and gas-dynamic functions calculated from the given geometric parameters of the vortex devices with the functions obtained from the averaged values. These data makes it possible to work out a range of variations in the parameters of the geometric design of vortex apparatuses by zones, parameters at the inlet, outlet, and degrees of separation, minimize the number of manufactured laboratory and semi-industrial vortex apparatuses, and unify a number of units. Compared with similar known separators, vortex apparatuses are proposed that reduce the cost of preparing raw materials in the grain mill area by a factor of tens due to the elimination of moving working parts, assemblies and screens.